Brain structure correlates of social information use: an exploratory machine learning approach - de Groot, Esra Cemre Su; Hofmans, Lieke; van den Bos, Wouter (Frontiers in Human Neuroscience, 2024)
Individual differences in social learning impact many important decisions, from voting behavior to polarization. Prior research has found that there are consistent and stable individual differences in social information use. However, the underlying mechanisms of these individual differences are still poorly understood. We used two complementary exploratory machine learning approaches to identify brain volumes related to individual differences in social information use. Using lasso regression and random forest regression we were able to capture linear and non-linear brain-behavior relationships.Consistent with previous studies, our results suggest there is a robust positive relationship between the volume of the left pars triangularis and social information use. Moreover, our results largely overlap with common social brain network regions, such as the medial prefrontal cortex, superior temporal sulcus, temporal parietal junction, and anterior cingulate cortex. Besides, our analyses also revealed several novel regions related to individual differences in social information use, such as the postcentral gyrus, the left caudal middle frontal gyrus, the left pallidum, and the entorhinal cortex.Together, these results provide novel insights into the neural mechanisms that underly individual differences in social learning and provide important new leads for future research.